Identification of Storynomics Tourism in the Production of an Animation “Barley Manusia Ikan" and its Audience Reception (Experimental Study on Tourism Communication Strategy for Super Priority Destinations) - Akmalia, Nurul; Yurmama, Trifajar; Widiargo, Antonius Edi; Rahmayanti, Handika Dany; Cempaka, Putri Surya (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The aim of making this animated film is to promote the national tourism priority area of Labuan Bajo in the form of an animated film by adapting the culture and way of life of the Bajo tribe. Labuhan Bajo is not only the beauty of the natural landscape and sea, the living culture of the Bajo tribe which can physically adapt to aquatic life is an attraction in the process of creating the main character design and story in Barley's animated short film "Fish Man". The data collection methods used range from creating creative designs to measuring audience responses using Google forms. The final result of developing the character design and story of Barley "Fish Man" is in the form of an animated short film which contains a description of each character, expressions and activities of each character with a duration of 7 minutes, and uses storynomics tourism storytelling techniques to increase tourist attraction and is expected to be able to promote Labuan Bajo and can improve the community's economy. The level of audience reception towards this animated film shows a positive response from the result of focused group discussions. Apart from that, 85,7—90% of the survei result stated that the assesment was in the adequate category, both in terms of character design and storyline.